Crystal alignment of surface stabilized polymorph in thioindigo films. (January 2020) - Rivalta, A.; Giunchi, A.; Pandolfi, L.; Salzillo, T.; S. d'Agostino,; Werzer, O.; Schrode, B.; Demitri, N.; Mas-Torrent, M.; Brillante, A.; Della Valle, R.G.; Venuti, E.
Abstract: Thioindigo (2-(3-Oxo-1-benzothiophen-2(3 H )-ylidene)-1-benzothiophen-3(2 H )-one) is a synthetic dye related to the natural compound Indigo. Notwithstanding the interest aroused recently by its employment as a functional material in a number of applications, a satisfactory characterization of its solid state is still missing. In this work, we study the occurrence of the two thioindigo α and β polymorphs under various growth conditions, and find that their structural similarity implies they often coexist. However, whereas polymorph β is certainly predominant in the bulk phase, polymorph α grows preferentially on substrates, turning out to be the surface stabilized phase in highly homogeneous and ordered films obtained by the bar‐assisted meniscus shearing method (BAMS). DFT calculations support the experimental findings, aiding in the polymorph spectroscopic identification and to the interpretation of the order in the films of polymorph α. Graphical abstract: Image 1 Highlights: The β polymorph, thought to be the less stable, is obtained in most of the common growth methods. The α polymorph is stabilized on a substrate, to the point of becoming the only phase present. BAMS technique supplies a control of the polymorphism and of the molecular alignment in film.